Esrrb-Cre Excises loxP-Flanked Alleles in Early Four-Cell Embryos - Lee, Sungeun (Genesis, 2015)
Among transgenic mice with ubiquitous Cre recombinase activity, all strains to date excise loxP-flanked (floxed) alleles, either at or before the zygote stage or at nondescript stages of development. This manuscript describes a new mouse strain, in which Cre recombinase, integrated into the Esrrb locus, efficiently excises floxed alleles in pre-implantation embryos at the onset of the four-cell stage. By enabling inactivation of genes only after the embryo has undergone two cleavages, this strain should facilitate in vivo studies of genes with essential gametic or zygotic functions. In addition, this study describes a new, highly pluripotent hybrid C57BL/6J × 129S1/SvImJ mouse embryonic stem cell line, HYB12, in which this knock-in and additional targeted alleles have been generated.